Preventing Microbial Infections with Natural Phenolic Compounds - Kardelen Ecevit; Alexandre A. Barros; Joana M. Silva; Rui L. Reis (MDPI AG, 2022)
The struggle between humans and pathogens has taken and is continuing to take countless lives every year. As the misusage of conventional antibiotics increases, the complexity associated with the resistance mechanisms of pathogens has been evolving into gradually more clever mechanisms, diminishing the effectiveness of antibiotics. Hence, there is a growing interest in discovering novel and reliable therapeutics able to struggle with the infection, circumvent the resistance and defend the natural microbiome. In this regard, nature-derived phenolic compounds are gaining considerable attention due to their potential safety and therapeutic effect. Phenolic compounds comprise numerous and widely distributed groups with different biological activities attributed mainly to their structure. Investigations have revealed that phenolic compounds from natural sources exhibit potent antimicrobial activity against various clinically relevant pathogens associated with microbial infection and sensitize multi-drug resistance strains to bactericidal or bacteriostatic antibiotics. This review outlines the current knowledge about the antimicrobial activity of phenolic compounds from various natural sources, with a particular focus on the structure-activity relationship and mechanisms of actions of each class of natural phenolic compounds, including simple phenols, phenolic acids, coumarin, flavonoids, tannins, stilbenes, lignans, quinones, and curcuminoids.